Deskripsi Muatan Nilai Pendidikan Karakter pada Buku Teks Siswa Kelas IV SD/MI Tema 1 Indahnya Kebersamaan Kurikulum 2013 - Desy Wulandari; Asmayani Salimi; Rio Pranata (ISLAMIKA, 2023)
This study aims to describe the value of education characters in the textbook fourth grade students SD/MI theme 1 the beauty of togetherness and describethe interrelation of the value of character education in each subjects. This study is a descriptive research method with using content analysis with a qualitative approach. Source data in this study is a textbook fourth grade students SD/MI theme 1. Technology data collection in this study is documentation. Data analysis techniques using Miles and Hubermen model which includes four stages, namely data collection, data reduction, data presentation, and data conclusion. The results of the study show that there are 5 values of character education in student textbooks that value of religious characters 31ntimes, nationalist appeared 38 times, independent appeared 8 times, mutual cooperation as much as 30 time with, and integrity as 1 times. Character education have linkage on each subjects, it is because value integrated character education on each subject so that participants students can gain knowledge and get information about the value character and apply it in everyday life.